2023
DOI: 10.7554/elife.83353
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin reduces podocyte lipotoxicity in experimental Alport syndrome

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are anti-hyperglycemic agents that prevent glucose reabsorption in proximal tubular cells. SGLT2i improves renal outcomes in both diabetic and non-diabetic patients, indicating it may have beneficial effects beyond glycemic control. Here, we demonstrate that SGLT2i affects energy metabolism and podocyte lipotoxicity in experimental Alport syndrome (AS). In vitro, we found that SGLT2 protein was expressed in human and mouse podocytes to a similar extent of tubu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…Soler, Cacha and Anders also showed concerns regarding the expression of SGLT2 in podocytes. The expression of SGLT2 can also be detected in the podocytes of Alport mice and mice with protein overload-induced proteinuria by immunofluorescence staining 6 7. We also observed SGLT2 expression in the proximal tubules, as demonstrated in the Results section.…”
supporting
confidence: 75%
“…Soler, Cacha and Anders also showed concerns regarding the expression of SGLT2 in podocytes. The expression of SGLT2 can also be detected in the podocytes of Alport mice and mice with protein overload-induced proteinuria by immunofluorescence staining 6 7. We also observed SGLT2 expression in the proximal tubules, as demonstrated in the Results section.…”
supporting
confidence: 75%
“…Recently, renoprotective effects (with a special focus on podocyte) of SGLT2 inhibitors have been revealed in proteinuric non-diabetic nephropathy, membranous nephropathy and Alport syndrome 15 39 40. Despite the local renoprotective effects on renal resident cells like podocytes, our data suggested that SGLT2 inhibitors might have systemic immunological regulation effect contributing to renal protection.…”
Section: Discussionmentioning
confidence: 68%
“…14,15 In vivo, empagliflozin monotherapy reduces albuminuria and prolongs the kidney survival of AS mice, however, unlike what has been observed in patients enrolled in DAPA-CKD or EMPA Kidney, the addition of empagliflozin to the standard of care (SOC) ramipril did not confer additional renoprotection, and overall, no difference across treatment groups was observed. 12 In another set of experiments, Ramipril monotherapy prolonged mean lifespan of Alport mice to 77.3±5.3 days with no additional benefit for dual ACE/SGLT2 inhibition, which prolonged mean lifespan to 80.3±11.0 days. 13 Of note, the Alport mouse model is fast progressive, so treatment effects in human patients with Alport syndrome should be better than in animal models.…”
Section: Main Textmentioning
confidence: 95%
“…(1) Insufficient pre-clinical evidence for efficacy and safety to translate data from old adults to children Two recent high quality pre-clinical studies, 12,13 raise concerns that in children with glomerular diseases SGLT2-inhibitors may not be -as solid and as foolproof -effective as in EMPA Kidney and DAPA-CKD patients who are 5 to 7 times their average age. 14,15 In vivo, empagliflozin monotherapy reduces albuminuria and prolongs the kidney survival of AS mice, however, unlike what has been observed in patients enrolled in DAPA-CKD or EMPA Kidney, the addition of empagliflozin to the standard of care (SOC) ramipril did not confer additional renoprotection, and overall, no difference across treatment groups was observed.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation